Design Color Sorting with Conveyor and Robot Arm Using Lego Mindstorms NXT - Yudhi Gunardi; Danang Fajar Kuncoro; Jumadril JN (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2021)
Lego Mindstorms education robot is an interactive robot because it can be used to design various kinds of robot applications. This robot can be used to design sorting robots before they are applied to real robots. Many sorting techniques are in the form of colorful objects, but only for one-time sorting. This research will design and implement a color sorting robot with 2 detection stages, namely the conveyor and the robot arm, the initial sorting is carried out by the conveyor for sorting color objects, the next sorting uses the robot arm. to move the selected color object to a place that matches the desired color. The results obtained in sorting color objects using 1 color sensor and Bluetooth for communication between the conveyor and the robot arm via Bluetooth works well where three objects in red, blue and green can be moved according to the desired color object.